Landšturmo giesmė. Lithuanian Poetry of the Napoleonic Wars - Citavičiūtė, Liucija (Senoji Lietuvos literatūra, 2024)
A printed booklet with no individual shelf mark within the overall file pagination is bound among the manuscripts in file 137-5 of the Liudvikas Rėza collection in the Wroblewski Library of the Lithuanian Academy of Sciences. The booklet bears only the title, Landšturmo giesmė (The Hymn of Landsturm), and neither the publishing data nor the author are given. The surname ‘Hassenstein’, written in Rėza’s handwriting in the corner suggests that it was he who prepared the booklet for printing.The booklet contains Lithuanian poems from the Napoleonic Wars. This article-publication establishes the circumstances and publishing details of the booklet, provides detailed information about the author, and assesses the historical and enduring value of Lithuanian poems. The publication is a rarity as only this particular copy is known.The biography and activities of the author, Christoph Daniel Hassenstein (1756-1821), have not yet been studied in detail. He was a priest in Piktupönen (Piktupėnai; at present, this church village on the Prussian-Lithuanian border is in the territory of Lithuania) all his life; here he produced significant works in Lithuanian studies: he wrote a history of the Napoleonic Wars (1814) in Lithuanian, which included 20 Lithuanian war songs and poems, translated the history of the Reformation (1818), and prepared a number of books of an educational nature for Lithuanians.Hassenstein’s poem ‘Pasipūtęsis svieto pergalėtojis’ (The Pompous Conqueror of the World), which ridicules Napoleon’s army beaten at the Battle of Leipzig, is one of the very few examples of early Lithuanian satire.
Keywords: Prūsijos Lietuva; Napoleono karų poezija; mūšis prie Leipcigo; Kristupas Danielius Hasenšteinas; Liudvikas Rėza